Taking wing - Graff, Nancy Price, 1953- (Clarion Books, 2005)
Thirteen-year-old Gus, sent to live with his grandparents in Vermont while his mother recovers from tuberculosis and his father serves in the Army Air Corps during World War II, learns lessons about life, responsibility, and friendship while hatching and raising a brood of orphaned ducks, and getting to know and understand his neighbor Louise Lavictoire.